The Role of Financing in the Development of Human Capital of Mining Industry: Modern Trends under Uncertainty - Frolova Viktoriia; Dolina Olga; Shpilkina Tatyana (E3S Web of Conferences, 2020)
The authors studied financing issues in the development of human capital in mining industry. They analyzed the distribution of financial resources in the field under current conditions of the economic activity decrease at the enterprises in connection with the spread of coronavirus infection. An assessment of the demand for vacancies by profession, region and wage level was made. The issues of enterprise personnel management in the form of a set of interacting and interconnected HR-technologies that allow enterprises to manage the staff and work more efficiently are studied. The authors concluded that an important aspect of the quality personnel training and the development of modern companies is a properly built system of improving the quality of human capital, as well as, measures for ensuring safety and preserving health, improving the qualification level, creating conditions for creativity and labor potential growth.